Knowledge and management of childhood constipation among South African Paediatric health care providers - Ramsunder, Sheethal (My University, 2022)
Introduction Functional constipation is a chronic disorder characterised by difficult, sporadic, or incomplete defaecation, without physiological or structural abnormalities, that does not meet the criteria for irritable bowel disease. Significant differences in knowledge and practice patterns exist regarding the approach to paediatric constipation. Objectives This study aimed to assess knowledge and practice patterns among paediatric health care providers in Gauteng province. Methods An online survey was disseminated via email and WhatsApp to doctors in the University of Witwatersrand paediatric circuit, as well as private paediatricians. The questionnaire assessed the participants’ demographic data, knowledge of pathophysiology, diagnostic criteria and danger signs, management and educational preferences for paediatric functional constipation. Results 139 responses were included in the study. There were widely varying levels of knowledge and management practices among all levels of healthcare providers. 48% of participants believed the most common cause for functional constipation ,was a low fibre intake, while only 36% indicated the cause was stool withholding. Most participants correctly identified the most obvious“red flags” in order to rule out organic causes of functional constipation. When diagnosing functional constipation in children, 66% of participants always use only a history and examination, 15% always use a digital rectal exam while 8% avoid them completely. In terms of treatment: Optimising fibre and fluid intake were routinely recommended by 66% and 71% respectively. 53% advise establishing a good toilet routine, while 19% endorse instituting a reward system. The most popular choice for disimpaction was fleet enemas (69%) with only 22% using polyethylene glycol (PEG). Lactulose rather than PEG was preferred for maintenance therapy regardless of the age of the child. There was no consensus on the duration of treatment necessary to treat functional constipation. Conclusion There is no unified approach to constipation, even among colleagues working in the same sector. We recommend that there should be more emphasis placed on this topic at an undergraduate level and at academic conferences. National guidelines on the management of paediatric functional constipation would optimise and streamline treatment strategies into a unified approach.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Paediatrics to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022